Ki-67 Labeling Index in Primary Invasive Breast Cancer from Sudanese Patients: A Pilot Study. (13th December 2012) - Awadelkarim, Khalid Dafaallah; Mariani-Costantini, Renato; Osman, Ihsan; Barberis, Massimo Costanzo
Abstract : Ki-67 labeling index has been linked to patient outcome in breast cancer patients. However, very few published reports have examined Ki-67 labeling index in African breast cancer patients. Sixty-two Sudanese breast cancer patients with primary invasive tumors were immunostained for Ki-67, ER, PR, Her-2/neu, CK5/6, and CK17. Ki-67 labeling index ranged from 0% to 50%, with a median of 5% (interquartile range 0–10). Low Ki-67 labeling index (immunostaining < 10%) was detected in 43/62 (69.4%) with a median of 0 (interquartile range 0–5), whereas high Ki-67 labeling index (immunostaining ≥ 10%) was revealed in 19/62 (30.6%) with a median of 20 (interquartile range 12–26). Ki-67 labeling index was significantly associated with tumor grade (P = 0.022, Mann-Whitney U Test). There were no significant group differences between Ki-67 labeling index and ER (P = 0.43 ), PR (P = 0.7 ), Her-2/neu (P = 0.45 ), CK5/6 (P = 0.29 ), CK17 (P = 0.55 ), pathologic stage (P = 0.4 ), tumor histology (P = 0.99 ), breast cancer subtypes (P = 0.47 ), tumor size (P = 0.16 ), and age at diagnosis (P = 0.6 ). These results suggested that Ki-67 labeling index correlates with tumor differentiation and not with the tumor size or any other tested marker in Sudanese breast cancers. Thus, Ki-67 labeling index could be considered as a reliable measure of tumor proliferative fraction in Sudan.